Analysis of the Influence of Human Development, Economic Growth, and Labor Indices on Poverty Levels in Sumenep Regency - Rahman, Moh. Syaiful; Primandhana, Wiwin Priana (Indonesian Journal Publisher, 2026)
This study aims to analyze the influence of the Human Development Index (HDI), Economic Growth, and Labor on the Poverty Level in Sumenep Regency. The data used is secondary data from the Central Statistics Agency (BPS) of Sumenep Regency and East Java Province for the 2012–2023 period. The analysis was carried out using the Multiple Linear Regression method with the help of the SPSS version 24 program. The results of the classical assumption test showed that the regression model met the criteria of normality, was free from multicollinearity, heteroscedasticity, and autocorrelation, so the model was declared feasible to use. The results of the study show that HDI has a negative and significant effect on the poverty rate, Economic Growth does not have a significant effect, and the Labor Force has a positive and significant effect on the poverty rate. The determination coefficient value (R²) of 95.1% shows that the model has a very high explanatory power, so that the results of this study can be trusted and accurately describe the empirical conditions in Sumenep Regency, while the remaining 4.9% is influenced by other factors outside the research model. These results confirm that improving human quality has the most dominant role in reducing poverty compared to other economic variables.